Tomato spotted wilt virus (tswv), weeds and thrip vectors in the tomato (solanum lycopersicum l.) in the andean region of cundinamarca (colombia) (2013)
ABSTRACT                                                                                            The presence and distribution of the TSWV, weeds and thrip vectors in major tomato producing areas in the Andean de- partment of Cundinamarca (Oriente, Sumapaz and Ubate provinces) were assessed with the DAS ELISA technique, evalu- ating the presence of the TSWV in tomato tissue, associated thrips and weeds. High incidences were observed in different provinces of the Andean department of Cundinamarca. The average viral incidence reached 23.3% in Sumapaz, 19.4% in Oriente and 4% in Ubate. The symptoms observed were: brown spots and concentric rings in the leaf area, stems and fruits; browning and spotting in the flower; and wilting in the leaves, stems and flowers. The thrip species with the highest presence were Frankliniella occidentalis, followed by Thrips palmi and Thrips tabaci. We determined the important role of weeds as inoculum sources and vector reservoirs for the species Emilia sonchifolia and Amaranthus dubius.